Clinical and prognostic significance of changes in haemoglobin concentration during 1 year of androgen‐deprivation therapy for hormone‐naïve bone‐metastatic prostate cancer. (30th May 2018) - Ebbinge, Maria; Berglund, Anders; Varenhorst, Eberhard; Hedlund, Per Olov; Sandblom, Gabriel; ,
Abstract : Objective: To estimate the strength of change in haemoglobin (Hb) concentrations during 1 year of androgen‐deprivation therapy (ADT) as a predictor of survival in hormone‐naïve patients with bone‐metastatic (Stage M1b) prostate cancer. Patients and Methods: The patients included in this study were taken from the randomised trial (number 5) carried out by the Scandinavian Prostate Cancer Group (SPCG), comparing parenteral oestrogen with total androgen blockade (TAB) in hormone‐naïve M1b prostate cancer. We identified 597 men where Hb measurements were made at enrolment, as well as at 3, 6 and 12 months of ADT. The time‐dependent impact of Hb concentration changes on overall survival (OS) was analysed using multivariate Cox proportional hazards analysis. The 10‐year OS according to increase/decrease in Hb concentration for the three treatment periods was demonstrated using Kaplan–Meier curves. Results: Multivariate analysis of changes in Hb concentration between baseline and 3 months showed better survival in patients with a decrease in Hb concentration (hazard ratio [HR] 1.42, 95% confidence interval [CI] 1.11–1.80) compared to those with an increase, whilst there was no difference in survival associated with a change in Hb concentration between 3 and 6 months (HR 0.93, 95% CI 0.76–1.12). Contrary to the first 3 months, poorer survival was seen in patients with a decrease in Hb concentration between 6 and 12 months (HR 0.76, 95% CI 0.62–0.92) compared to those with an increase. Conclusions: In a large cohort of Scandinavian men with hormone‐naïve M1b prostate cancer, an increase in Hb concentration between baseline and 3 months of ADT was associated with significantly poorer survival, whereas an increase between 6 and 12 months was associated with better survival. These findings provide new information about patterns of change in Hb concentrations during 12 months of ADT for M1b prostate cancer, and survival. Clinicians should be aware of the prognostic value of Hb concentration changes during ADT in M1b prostate cancer.